Number of positive lymph nodes affects outcomes in parotid adenoid cystic carcinoma - Han, Feng (Frontiers in Oncology, 2023)
Objectives Survival significance of the number of positive lymph nodes (LNs) in parotid adenoid cystic carcinoma (ACC) remains unknown; thus, this study aimed to determine the impact of the number of positive LNs on the prognosis of parotid ACC. Methods Patients with surgically treated parotid ACC were enrolled from the SEER database. The number of positive LNs was analyzed using three models (0 vs 1+, 0 vs 1 vs 2 vs 3 vs 4 vs 4 vs 5 vs 6+, 0/1 vs 2–4 vs 5+), its hazard ratios on disease specific survival (DSS) and overall survival (OS) were assessed using univariate and multivariate Cox analyses. Results A total of 1,689 patients were included. In all models, the number of positive LNs was independently related to DSS and OS, model 3 had the highest C-index for DSS [0.83 (95% CI: 0.81–0.85)] and OS [0.82 (95% CI: 0.80–0.84)]. Compared with the 0/1 positive LN group, the 2–4 positive LN group had an HR of 2.81 (95% CI: 1.73–4.56) for DSS and 2.36 (95% CI: 1.58–3.54) for OS. The 5+ LN group had an HR of 20.15 (95% CI: 7.50–54.18) for DSS and 14.20 (95% CI: 5.45–36.97) for OS. No overlap existed in the 95% CI of the HR. Conclusions The three prognostic categories based on the number of positive LNs (0/1 vs 2–4 vs 5+) could stratify the DSS and OS in parotid ACC without overlap.